Activity-dependent conformational transitions of the insulin receptor–related receptor - Batishchev, Oleg V. (J Biol Chem, 2021)
The insulin receptor (IR), insulin-like growth factor 1 receptor (IGF-1R), and insulin receptor-related receptor (IRR) form a mini family of predimerized receptor-like tyrosine kinases. IR and IGF-1R bind to their peptide agonists triggering metabolic and cell growth responses. In contrast, IRR, despite sharing with them a strong sequence homology, has no peptide-like agonist but can be activated by mildly alkaline media. The spatial structure and activation mechanisms of IRR have not been established yet. The present work represents the first account of a structural analysis of a predimerized receptor-like tyrosine kinase by high-resolution atomic force microscopy in their basal and activated forms. Our data suggest that in neutral media, inactive IRR has two conformations, where one is symmetrical and highly similar to the inactive Λ/U-shape of IR and IGF-1R ectodomains, whereas the second is drop-like and asymmetrical resembling the IRR ectodomain in solution. We did not observe complexes of IRR intracellular catalytic domains of the inactive receptor forms. At pH 9.0, we detected two presumably active IRR conformations, Γ-shaped and T-shaped. Both of conformations demonstrated formation of the complex of their intracellular catalytic domains responsible for autophosphorylation. The existence of two active IRR forms correlates well with the previously described positive cooperativity of the IRR activation. In conclusion, our data provide structural insights into the molecular mechanisms of alkali-induced IRR activation under mild native conditions that could be valuable for interpretation of results of IR and IGF-IR structural studies.